2012
DOI: 10.1124/dmd.112.048322
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Blood-Brain Barrier and Restriction of Drug Delivery to Invasive Glioma Cells: Findings in an Orthotopic Rat Xenograft Model of Glioma

Abstract: Despite aggressive treatment with radiation and chemotherapy, recurrence of glioblastoma multiforme (GBM) is inevitable. The objective of this study was to show that the blood-brain barrier (BBB), through a combination of tight junctions and active efflux transporters in the brain microvasculature, can significantly restrict delivery of molecularly targeted agents to invasive glioma cells. Transgenic mice lacking P-glycoprotein (P-gp) and breast cancer resistance protein (Bcrp) were used to study efflux of erl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
112
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 33 publications
2
112
1
Order By: Relevance
“…Approximately 10% of NSCLC patients in the Western population harbor an activating mutation in their EGFR genes (e.g., the exon 19 deletion delE746-A750 or the exon 21 point mutation L858R) resulting in higher response rates to treatment with erlotinib or gefitinib, another EGFR-inhibiting TKI, as compared with patients with wild-type EGFR (1). 11 C-erlotinib has been proposed as a PET tracer to distinguish erlotinib-sensitive from erlotinibresistant NSCLC patients (2,3). In preclinical PET studies, higher uptake of 11 C-erlotinib was found in tumor xenografts with activating EGFR mutations (e.g., delE746-A750, L858R) than in tumor xenografts expressing wild-type EGFR or EGFR with secondary resistance causing mutations (exon 20 missense mutation T790 M) (2,(4)(5)(6).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 10% of NSCLC patients in the Western population harbor an activating mutation in their EGFR genes (e.g., the exon 19 deletion delE746-A750 or the exon 21 point mutation L858R) resulting in higher response rates to treatment with erlotinib or gefitinib, another EGFR-inhibiting TKI, as compared with patients with wild-type EGFR (1). 11 C-erlotinib has been proposed as a PET tracer to distinguish erlotinib-sensitive from erlotinibresistant NSCLC patients (2,3). In preclinical PET studies, higher uptake of 11 C-erlotinib was found in tumor xenografts with activating EGFR mutations (e.g., delE746-A750, L858R) than in tumor xenografts expressing wild-type EGFR or EGFR with secondary resistance causing mutations (exon 20 missense mutation T790 M) (2,(4)(5)(6).…”
mentioning
confidence: 99%
“…In NSCLC patients, it was shown that the distribution volume of 11 C-erlotinib was significantly higher in tumors with an exon 19 deletion than in tumors with wild-type EGFR (3). Apart from visualizing the EGFR mutational status of tumors, 11 C-erlotinib PET may also be of interest to predict the distribution of erlotinib to different body tissues targeted for erlotinib treatment (e.g., lung, brain, liver).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, BMVECs concentrate the expression of P-gp, a member of the ATPbinding cassette (ABC) superfamily of proteins, to the luminal surface, where P-gp acts as an efflux transporter, removing a variety of diverse chemical structures away from the brain parenchyma [163]. The function of P-gp (and the redundant function of the related multi-drug resistant proteins) has been well defined as one of the most significant challenges to delivering chemotherapeutic agents to parenchymal brain cells and tumor cells in the CNS; furthermore, the BBB has proven no less challenging for the delivery of DNA-based therapies to CNS targets [165][166][167].…”
Section: Blood-brain Barriermentioning
confidence: 99%